Pelatih Ketrampilan Manajemen Marah untuk Agresi Verbal Orang Dewasa dengan Gangguan Psikotik Singkat - Yanuarty Paresma Wahyuningsih (Universitas Islam Indonesia, 2016)
The purpose of this study is to test the effectiveness of anger management skill training to reduce verbal aggression level. With a single case design, a 24 years man who had a brief psychotic disorder participated this study. Data were collected by interview, observation, and behavior checklist. Anger management skill training was delivered in six sessions. Data analysis showed that the verbal aggression frequency of the patient decrease, from five times to once a day. Key words: anger management skill training, verbal agression, brief psychotic disorder